PROBIOTIC Bacillus subtilis AND Lactobacillus plantarum IN DIET OF NILE TILAPIA - Mateus Cardoso Guimarães; Danielle de Carla Dias; Felipe von Atzingen Pereira de Araujo; Carlos Massatoshi Ishikawa; Leonardo Tachibana (Boletim do Instituto de Pesca)
The aim of this study was to evaluate the effects of a probiotic, composed of Bacillus subtilis and Lactobacillus plantarum in Nile tilapia fry during the sex reversal phase under stress conditions caused by high stocking density. This experiment was conducted in the Fisheries Institute of São Paulo. The experiment design was completely randomized with four treatments: 1) probiotic added feed, 2) probiotic added to water, 3) probiotic added to feed and water and 4) control diet; with three replicates. The variables analyzed were: final weight, total length, specific growth rate, survival, intestinal microbiology and gene expression of TNF-Î± and HSP-70. The results of the zootechnical performance of growth and gene expression did not show significant differences between treatments in the parameters evaluated (P>0.05). In the intestinal tract of fry raised in water with added probiotic, log10 CFU (7.72 Â± 0.51) count of Bacillus spp. was higher than with other treatments which themselves did not differ significantly. It was concluded that the addition of a probiotic of Bacillus subtilis and Lactobacillus plantarum in the feed or water of Nile tilapia fry during the sex reversal phase did not affect the zootechnical performance of growth or expression the genes studied, but modified the intestinal microbiota.